Propuesta de un instrumento para la evaluación de sostenibilidad y competitividad de empresas turísticas - Atiaja Jiménez, Viviana Lisbeth (2023)
Competitive and sustainable quality services can be a motivation for the permanence of tourists. However, in Ecuador, there is no analysis of these variables and their influence on the development of tourism companies, which affects the quality of the service offered. In the present research, it is proposed to design a tool to collect information on these two factors, which can later be applied in tourism companies in Ecuador and thus propose continuous improvement strategies. To meet the objective, a bibliographic analysis of different authors was carried out, conducting a characterization of the existing instruments based on sustainability and competitiveness. These instruments are generally analyzed separately, however, for the proposal a single tool was established for the two variables, but it was considered that the perspective of the managers and owners varies from that of the tourists. For this reason, two different tools were designed for them. Through a comparative table, it was determined that there are dimensions and sub-dimensions, and each dimension has sub-dimensions. This analysis was carried out separately but the present proposal integrates the two study variables, considering the outstanding ones, which are economic (7 for managers and tourists), sociocultural (9 for managers and 8 for tourists), environmental (9 for managers and 10 for tourists), the development of ICTs (9 for managers and 6 for tourists), support elements (13 for managers and 9 for tourists) and tourist service (8 for managers and 8 for tourists); obtaining a tool for tourists of 47 items, and for managers or owners of 55. A pre-validation was carried out using the expert judgment methodology (2), granting evaluation criteria to assess the sufficiency, clarity, coherence, and relevance, through the Likert scale. A result of 42 out of 44 was obtained, which initially demonstrates that the designed tool has adequate characteristics for its application. Adjustments were made to the tools for their pilot project to two hotels in the city of Latacunga, both the Oro Verde hotel and the Rodelu hotel. The results were unified to establish a mitigation plan for the main problems of the establishments that in their overall rating obtained a level of sustainability and competitiveness of 67.90% around the administrative area. But, for tourists, there was a lower percentage that was 59.8%. In the mitigation and continuous improvement plan, environmental factors were identified, because they contribute significantly to the sustainable and sustainable use of the hotel's renewable and non-renewable resources, such as visual and auditory pollution, energy, and water savings. Based on the above, it can be concluded that it is possible to unify the criteria of sustainability and competitiveness in a single tool. But, it is important to differentiate a tool for tourists, because there is a difference between the two values obtained. Therefore, it is advisable to perfect this tool before its application.